PERAN ORANG TUA DALAM PENDIDIKAN AGAMA ISLAM DI DESA TANJUNG LALAK UTARA KECAMATAN PULAU LAUT KEPULAUAN KABUPATEN KOTABARU - Rachmad Hayat; Nur Hasan; Imam Safi’i (VICRATINA, 2022)
The main role that parents must play is to instill religious education in children from an early age because, as previously explained, the family is the first and foremost madrasa institution that has a major influence on children until they grow up. The supporting factor needed apart from parental awareness is the willingness of the child to receive education from his parents. Tanjung Lalak Utara, Pulau Laut Archipelago District, is a village located in Kotabaru district, South Kalimantan province, where the majority of the people are Muslim. The mosque and prayer room contained therein are used for worship such as the 5 daily prayers and major Islamic events and recitations which are held about once a month. Even so, it is rare to find children and teenagers there coming to the mosque and recitation. Besides, their behavior is still far from expected. It can be seen from their daily behavior that there are many problems and many cases of complaints from parents and teachers regarding their behavior. Besides that, the environment in Tanjung Lalak is still not supportive because there are still many inhibiting factors that can threaten such as promiscuity, pornography, and narcotics that can damage the future of a child. Therefore, it is important to examine the role of Muslim parents in Tanjung Lalak regarding Islamic religious education for their children.